Soybean Cost-Return Budget in Northeast Kansas - O'Brien, Daniel M.; Duncan, Stewart R. (My University, 2009)
This publication projects a budget that reflects expected income and costs based on typical soybean production practices in northeastern Kansas.
MF570_2009_12
Keywords: MF570; Economics; Crops; MF